The United States of America and the Malayan Emergency, 1948-1960: A Literature Review (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
This manuscript focuses on discussions of the historiography of the emergency in Malaya from 1948 to 1960, which holds a connection with the United States of America. The main objective of this study is to analyse previous studies on the emergency in Malaya by focusing on the question of the United States’ involvement in the conflict, whether it be directly or indirectly. The focus on this issue is to show that the United States had a connection with the emergency because of its usual attention given to the British, who were the main character in the conflict in Malaya. Without excluding the British in Malaya during the emergency, this historiographical study also sheds light upon the position of this imperialist country in other Commonwealth countries throughout the event. Qualitative method was used in this study through the analysis of past papers related to the emergency, as furthest as can be. Studies in the form of theses, books, paperwork, and journal articles were analysed to produce a more objective discussion. Based on the findings, it can be concluded that the historiography of the emergency in Malaya has a connection with the United States, and indeed consists of its own significance in acting as evidence of their direct and indirect interference in the 12 years of conflict.